Slope stability analysis and stabilization methods - Rangarajan, Saranya (Nanyang Technological University, 2020)
Slope stability is of great importance in the field of geotechnical engineering. The assessment of slope stability is of utmost importance as slope failures can lead to detrimental effects such as loss of lives. This report compares two commonly used methods in analysing slope stability which are Limit Equilibrium Method (LEM) and Finite Element Method (FEM). There are various commercial software available for engineers to analyse slope stability and stabilisation methods. In this paper, three different slope problems will be analysed using four types of software that are categorised into LEMs and FEMs. The four software are Slide 2018, Microsoft Excel which uses LEM, RS2, PLAXIS 2D which uses FEM to calculate the factor of safety (FOS) of the slope. The critical slip surface and the corresponding FOS obtained from each software will be compared and discussed in detail. The results from both methods are generally accurate and acceptable for engineering use. However, the author recommends using both LEM and FEM to verify the accuracy of the analysis. Lastly, various slope stabilisation methods will be discussed and a real case study on slope stabilisation will be evaluated by the author.